Determination of the Extension Strength of the Press Spring of the Parallelogram Mechanism of the Combined Disc Harrow (Eurasian Journal of Engineering and Technology, 2023)
The article presents the results of theoretical studies to determine the tension force of the compression spring of the parallelogram mechanism of the combined disk harrow of the leveler-compacter. In the course of the research, analytical expressions were obtained to determine the tension force of the pressure spring, on the basis of which it was determined that the tension force of the pressure spring of the parallelogram mechanism should be 452 N in order for the planer-compacter teeth to sink into the soil to a given depth.